Growth-Promoting and Antioxidant Effects of Magnolia Bark Extract in Chickens Uninfected or Co-Infected with Clostridium perfringens and Eimeria maxima as an Experimental Model of Necrotic Enteritis. Issue 4 (30th January 2018) - Oh, Sungtaek; Gadde, Ujvala Deepthi; Bravo, David; Lillehoj, Erik P; Lillehoj, Hyun S
Abstract: Background: Magnolia tree bark has been widely used in traditional Asian medicine. However, to our knowledge, no studies have been reported investigating the effects of dietary supplementation with magnolia bark extract in chickens. Objective: We tested the hypothesis that dietary supplementation of chickens with a Magnolia officinalis bark extract would increase growth performance in uninfected and Eimeria maxima / Clostridium perfringens co-infected chickens. Methods: A total of 168 chickens were fed from hatch either a standard diet or a diet supplemented with 0.33 mg or 0.56 mg M. officinalis bark extract/kg (M/H low or M/H high, respectively) from days 1 to 35. At day 14, half of the chickens were orally infected with E. maxima, followed by C. perfringens infection at day 18 to induce experimental avian necrotic enteritis. Daily feed intake, feed conversion ratio, body weight gain, and final body weight were measured as indicators of growth performance. Serum α1-acid glycoprotein (AGP) concentrations were measured as an indicator of systemic inflammation, and intestinal lesion scores were determined as a marker of disease progression. Transcript levels for catalase, heme oxygenase 1, and superoxide dismutase in the intestine, liver, spleen, and skeletal muscle were measured as indicators of antioxidant status. Results: Growth performance increased between days 1 and 35 in uninfected and E. maxima / C. perfringens co-infected chickens fed M/H-low or M/H-high diets compared with unsupplemented controls. Gut lesion scores were decreased, whereas AGP concentrations were unchanged, in co-infected chickens fed magnolia-supplemented diets compared with unsupplemented controls. In general, transcripts for antioxidant enzymes increased in chickens fed magnolia-supplemented diets compared with unsupplemented controls, and significant interactions between dietary supplementation and co-infection were observed for all antioxidant enzyme transcript levels. Conclusion: Magnolia bark extract might be useful for future development of dietary strategies to improve poultry health, disease resistance, and productivity without the use of antibiotic growth promoters.